PERTANGGUNGJAWABAN PIDANA INDIVIDU DALAM HUKUM PIDANA INTERNASIONAL - Danel Aditia Situngkir (Kajian Hukum, 2019)
ABSTRACT            The debate about the whereabouts of individuals as the subject of international law over time seems to get an answer. This is because after the first and second world wars, the international community's attention to human rights is increasing. The desire to bring the responsible perpetrators to account before the criminal court. Efforts to eliminate immunity against perpetrators for crimes committed encourage the establishment of international criminal tribunals ranging from the ad hoc nature to the permanent criminal court. Encouraging individuals as the rights and obligations in international criminal law is getting stronger. Be interesting because the individuals who are held accountable are citizens who actually have the sovereignty to enforce the law to their citizens. This paper will discuss the existence of individuals as subjects of international law and the effort to hold individuals accountable through international court mechanisms. The research method used is normative juridical. Based on legal theory, legal principles, sources of international law and international treaties. From the discussion it is concluded that the existence of individuals in international law can be seen from the granting of rights and obligations in international treaties. The Adhoc and Permanent International Criminal Court is established to demand the accountability of serious crimes against humanity.Keywords : Criminal Responsibility, Individual, International Criminal Law